SEMIOTIC ANALYSIS OF ROLAND BARTHES’S THEORY ON COMMUTER LINE (KRL) SIGNS - Galang Sapta Reswara; Hasna Maritza; Ika Rantantra Pujawali; Rahma Iftita Putri (Argopuro: Jurnal Multidisiplin Ilmu Bahasa, 2024)
Abstract This study examines the semiotic elements of signs within Indonesia's Commuter Line (KRL) system through Roland Barthes’s theory of denotation, connotation, and myth. Public signs are important in shaping commuter behavior by promoting safety, cleanliness, and order in shared spaces. The analysis highlights the dual meanings embedded in the signs, from their immediate messages, such as prohibiting smoking or ensuring evacuation preparedness, to the cultural values they reflect, such as health, environmental responsibility, and respect for public spaces. Through a qualitative approach, the research reveals how these signs not only guide actions but also mirror societal norms and priorities. By linking Barthes’s semiotic framework to practical signage design, this research underscores the importance of effectively communicating rules and values in public transportation systems. Keywords: Semiotic, Signs, Ronald Barthes, Commuter Line, KRL, Transportation